VERTICALIZATION AND INNOVATIVE ACTIONS: AN INVESTIGATION IN AGRICULTURAL COOPERATIVES IN GOIÁS - Sarmento Costa, Maria Elisa (2023)
The objective is to analyze the existence of a difference between the cooperatives that focus their verticalization upstream and downstream and the exploitation and exploration actions, respectively, in agricultural cooperatives in Goias. The study was carried out by applying a questionnaire to cooperatives, for which 35 valid responses were obtained. Data were analyzed using non-parametric mean tests (Mann-Whitney). The results found show that cooperatives that carry out activities upstream of the chain (Supply of Inputs and Technical Assistance and Rural Extension) have a higher average for exploitation actions when compared to cooperatives that do not carry out such activities and downstream of the production chain, the cooperatives that develop (Technical Assistance and Rural Extension) also have a higher average for the exploration actions when compared to the others, as for the activities carried out downstream of the production chain, the Industrialization of Production and Commercialization of Production activities, for which there was no significance, it was observed that mainly the Industrialization of Production activity needs investments to be carried out. The research made it possible to understand the structure of the productive chain of agricultural cooperatives in the state of Goias, based on the discussions presented about agrifood markets, the fragmentation of consumer preferences and the need to create new products as a competitive strategy, demonstrates the need to make investments in order to make such cooperatives more competitive in the current scenario.   DOI: 10.18226/23190639.v10n2.02